Arrestee Drug Abuse Monitoring (ADAM) Program in the United States, 1999 ([Verlag nicht ermittelbar], 2000)
The Arrestee Drug Abuse Monitoring (ADAM) Program, the successor to the Drug Use Forecasting (DUF) Program (DRUG USE FORECASTING IN 24 CITIES IN THE UNITED STATES, 1987-1997 [ICPSR 9477]), measures levels of and trends in drug use among persons arrested and booked in 35 sites across the United States. The data address the following topics: (1) types of drugs used by arrestees (based on self-reports and urinalysis), (2) self-reported dependency on drugs, (3) self-reported need for alcohol/drug treatment, (4) the relationship between drug use and certain types of offenses, and (5) the relationship between self-reported indicators of drug use and indicators of drug use based on urinalysis. Participation in the project is voluntary, and all information collected from the arrestees is anonymous and confidential. The data include the arrestee's age, race, gender, educational attainment, marital status, and the charge at the time of booking. The modified ADAM/DUF interview instrument (used for part of the 1995 data and all of the 1996, 1997, 1998, and 1999 data) also collected information about the arrestee's use of 15 drugs, including recent and past use (e.g., 3-day and 30-day drug use), age at first use, and whether the arrestee had ever been dependent on drugs. As part of the ADAM program, arrestees were asked to provide a urine specimen, which was screened for the presence of ten drugs, including marijuana, opiates, cocaine, PCP, methadone, benzodiazepines (Valium), methaqualone, propoxyphene (Darvon), barbiturates, and amphetamines (positive test results for amphetamines were confirmed by gas chromatography).